Development and Validation of LC Method for the Determination of Famciclovir in Pharmaceutical Formulation Using an Experimental Design - Srinivas Vishnumulaka; Narasimha Rao Medicherla; Allam Appa Rao; G. Edela Srinubabu (E-Journal of Chemistry)
A rapid and sensitive RP-HPLC method with UV detection (242 nm) for routine analysis of famciclovir in pharmaceutical formulations was developed. Chromatography was performed with mobile phase containing a mixture of methanol and phosphate buffer (50:50, v/v) with flow rate 1.0 mL min−1. Quantitation was accomplished with internal standard method. The procedure was validated for linearity (correlation coefficient =0.9999), accuracy, robustness and intermediate precision. Experimental design was used for validation of robustness and intermediate precision. To test robustness, three factors were considered; percentage v/v of methanol in mobile phase, flow rate and pH; flow rate, the percentage of organic modifier and pH have considerable important effect on the response. For intermediate precision measure the variables considered were: analyst, equipment and number of days. The RSD value (0.86%, n=24) indicated an acceptable precision of the analytical method. The proposed method was simple, sensitive, precise, accurate and quick and useful for routine quality control.